Microarray-in-a-Tube for Detection of Multiple Viruses - Liu, Quanjun (Clin Chem, 2007)
Background: The detection of multiple viruses is important for pathogenic diagnosis and disease control. Microarray detection is a good method, but requires complex procedures for multiple virus detection. Methods: We developed a novel PCR assay, the microarray-in-a-tube system, which integrates multiple PCR processes and DNA microarrays for multiple virus detection. A 5 × 5 oligonucleotide microarray for detecting 4 respiratory tract viruses (severe acute respiratory syndrome–associated coronavirus, influenza A virus, influenza B virus, and enterovirus) with inner controls was arranged on the inner surface of a specially designed Eppendorf cap with a flat, optically transparent window. Results: We were able to perform all detection processes in the encapsulated system without opening the cap. The 4 viruses were successfully amplified by one-step reverse transcription–PCR in the encapsulated tube. After the PCR process, the microarray-in-a-tube was inverted, and the fluorescence-labeled PCR products were directly hybridized on the microarray. Hybridization signals were obtained with an ordinary fluorescent microscope. The sensitivity of the system for virus detection reached 10(2) copies/μL. With the help of inner controls, the system provided reliable results without false negatives and false positives. Conclusions: The microarray-in-a-tube system is a rapid, labor-saving tool for multiple virus detection with several advantages, such as convenience, prevention of cross-contamination of the PCR products, and potential for multiple-gene detection.